Assessing Amino Acid Metabolism in Splanchnic Tissues and Mammary Glands to Short-Term Graded Removal of Lys From an Abomasal-Infused Amino Acid Mixture in Lactating Goats - Li, Yantao; Lin, Xueyan; Liu, Chen; Hu, Zhiyong; Hou, Qiuling; Wang, Zhonghua (Frontiers in Veterinary Science, 2022)
To investigate responses of amino acid metabolism in portal-drained viscera, liver and peripheral tissues (included mammary) to a graded decrease of postruminal Lys supply, four multi-catheterized lactating goats were used in a 4 × 4 Latin square experiment. Goats were fasted for 12 h and then received a 33 h abomasal infusion of an amino acid mixture and glucose. Treatments were graded decrease of Lys content in the infusate to 100 (complete), 60, 30 or 0% as in casein. Lys-removed infusions decreased production of milk, milk protein, fat and lactose linearly and also decreased arterial Lys concentrations linearly (P<0.05). Net PDV uptake decreased linearly (P<0.05) with the decreased loss ratio in the PDV (P<0.05). Although liver removal of Lys decreased linearly (P<0.05), the removal ration relative to portal absorption changed small which was about 10% at the four treatments, indicating the liver can remove Lys in a fixed proportion. Reduced Lys supply resulted in a linear decrease utilization of Lys in the peripheral tissues (not include mammary, P<0.05) and release more Lys to mammary glands. Although net mammary uptake of Lys declined linearly (P<0.05), the lactating goats can partially offset the negative effect of decreased circulating Lys concentrations through increased mammary affinity and increased mammary blood flow. Graded removal of Lys from the infusate linearly decreased mammary uptake-to-output ratios of Lys (P<0.05) suggesting that mammary catabolism of Lys decreased. Meanwhile, treatments linearly increased the circulating concentrations of glucagon and linearly decreased prolactin (P<0.05). In conclusion, results of the present study indicated there were several mechanisms used to mitigate a Lys deficiency, including reduced catabolism of Lys in PDV and peripheral tissues (including mammary glands) and linearly increases in mammary blood flow and mammary affinity together with the increased mammary uptake and U:O of BCAA. Given these changes, the decline in milk protein production could be attributed to combined effect of mass action with Lys and hormonal status.